2013
DOI: 10.1680/macr.12.00149
|View full text |Cite
|
Sign up to set email alerts
|

Energy-based seismic performance of reinforced concrete frame structures

Abstract: The distribution of structural hysteretic energy is significant in energy-based seismic performance evaluations of reinforced concrete (RC) structures. This research involved the design of a six-storey RC frame and analysis of its dynamic time history for typical ground motions. Based on a comparison of the numerical results of the earthquake input energy and structural hysteretic energy under minor, moderate and major levels of earthquakes of grades 8 and 9, the allocation and distribution of structural hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The indicator , however, may underestimate the real damage extent of structures subjected to earthquakes since the structural ultimate state was not considered. Consequently, some authors modified the form of initial stiffness over reduced secant stiffness ratio and suggested a new damage index as given below [12] 0 0 ,…”
Section: Stiffness-based Indicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The indicator , however, may underestimate the real damage extent of structures subjected to earthquakes since the structural ultimate state was not considered. Consequently, some authors modified the form of initial stiffness over reduced secant stiffness ratio and suggested a new damage index as given below [12] 0 0 ,…”
Section: Stiffness-based Indicesmentioning
confidence: 99%
“…In this regard, a building would survive an earthquake with the energy dissipation capacity above the earthquake input energy. Therefore, the energy dissipation capacity can be utilized as a key indicator to measure damage in structures [13]. As shown in Fig.1., an energy coefficient is employed as a damage index expressed as:…”
Section: Energy-based Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Structures in earthquake damage effect depend on the dynamic characteristics of earthquake and dynamic characteristics of structure. Seismic dynamic characteristic can be determined by seismic amplitude of vibration, frequency and duration to describe; structural dynamic characteristics including natural period of vibration, vibration and damping [7]. China's seismic design [8] specification: Special irregular building, a building and the specific conditions of the high-rise buildings should adopt the time-history analysis method for calculating.…”
Section: The Time-history Dynamic Analysis Of High-rise Structure Undmentioning
confidence: 99%